An Empirical Analysis on Cost Efficiency and Profitability Determinants of Commercial Banks in China - Wu, Hui-yu (2019)
The development of Chinese commercial banks is not only vital to the domestic economy but also affects the world economy. The paper emphasizes the estimation of determinants of profitability and cost efficiency for commercial banks in China. The case period is from 2013 to 2018, and the sample is top 40 banks(ranked by total assets). SFA estimator is applied to calculate cost efficiency, and system GMM is used to analysis the banks’ profitability. The results imply the efficiency of foreign-funded commercial banks is the best, and the overall trend of efficiency for banks is decreasing. As for bank profitability, all the macroeconomic factors are essential in determining, so the external environment is important. Besides, the increase in cost efficiency and asset quality can boost bank performance.